Ambient Ammonia Electrosynthesis: Current Status, Challenges, and Perspectives - Lv, Xian‐Wei; Weng, Chen‐Chen; Yuan, Zhong‐Yong (ChemSusChem, 2020)
Ammonia (NH3) electrosynthesis from atmospheric nitrogen (N2) and water is emerging as a promising alternative to the energy‐intensive Haber–Bosch process; however, such a process is difficult to perform due to the inherent inertness of N2 molecules together with low solubility in aqueous solutions. Although many active electrocatalysts have been used to electrocatalyze the N2 reduction reaction (NRR), unsatisfactory NH3 yields and lower Faraday efficiency are still far from practical industrial production, and thus, considerable research efforts are being devoted to address these problems. Nevertheless, most reports still mainly focus on the preparation of electrocatalysts and largely ignore a summary of optimization–modification strategies for the NRR. In this review, a general introduction to the NRR mechanism is presented to provide a reasonable guide for the design of highly active catalysts. Then, four categories of NRR electrocatalysts, according to chemical compositions, are surveyed, as well as several strategies for promoting the catalytic activity and efficiency. Later, strategies for developing efficient N2 fixation systems are discussed. Finally, current challenges and future perspectives in the context of the NRR are highlighted. This review sheds some light on the development of highly efficient catalytic systems for NH3 synthesis and stimulates research interests in the unexplored, but promising, research field of the NRR. Activating the inert: Ammonia electrosynthesis from atmospheric nitrogen and water is emerging as a promising alternative to the energy‐intensive Haber–Bosch process. The inherent inertness of N2 molecules, together with low solubility in aqueous solutions, make this process challenging. Electrocatalytic artificial nitrogen fixation for ammonia synthesis under mild conditions is reviewed.